Reputasi KAP Sebagai Pemoderasi Financial Distress dan Efektivitas Komite Audit Terhadap Ketepatan Waktu Pelaporan Keuangan - Sayang Putri Pradnyani, Anak Agung Istri; Budiadnyani, Ni Putu (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the effect of financial distress and audit committee effectiveness on the timeliness of financial reporting, as well as the moderating role of audit firm reputation. This study employs a quantitative approach using secondary data from annual financial statements of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The sample was selected using purposive sampling. Financial distress is measured using the Debt to Asset Ratio (DAR), audit committee effectiveness is measured through audit committee independence, the number of professional members, and meeting frequency, audit firm reputation is measured by Big Four affiliation, while financial reporting timeliness is measured using a dummy variable. Data analysis was conducted using logistic regression with interaction moderation testing. The results show that financial distress and audit committee effectiveness have a positive effect on financial reporting timeliness. In addition, audit firm reputation strengthens the effect of both variables on financial reporting timeliness. This study concludes that audit firm reputation plays an important role in enhancing transparency and the timeliness of financial reporting in publicly listed companies.